(untitled) (Bulletin KNOB, 1990)
With the institution of BOOR, the Office for Archaeological research of Municipal works Rotterdam in 1960, ing. C. Hoek was the first archaeologist in municipal service. Rotterdam being a world harbour characterized by urban and industrial growth, from the beginning archaeological research comprised the entire region. BOOR’s regional action has been arranged formally through the Coordination Advisory Committee concerning archaeological research within the department of Rotterdam. Different municipalities and social sections are represented in this committee, which discusses the effects of planological developments on archaeological and socio-historical values and provides for information on this field as well. After the bombardment of the 10th of May 1940 one also expected the soil archives in the nucleus of the town to be destroyed. Later on historical research and archaeological measurements could localize pre-urban Rotterdam and connect these discoveries with the Rotta of 1028, which probably has been destroyed by inundations in 1164. Since 1988 the construction of the Willemspoor-subway is being accompanied archaeologically by BOOR. In this tracé, the history of Rotterdam from the 8th till the 19th century can be read on several spots. After World War II industrial and urban growth affected the soil archives of the rural area surrounding Rotterdam on numerous spots. Archaeological research was extremely necessary. Around the Maas-mouth one discovered hunting and fishing tools from the Mesolithic (8000 BC). In Rotterdam-IJsselmonde a Mesolithic encampment (ca. 5000 BC) with artefacts from the culture of Vlaardingen (3000 BC) could be localized. Medieval and Roman material as well as material from the Iron Age has been found in Rotterdam-Hartelkanaal. During the Roman period the area surrounding the Maas-mouth has been inhabited by an agricultural population. Skeletons from a burial field of the Roman period in Spijkenisse reveal facts on the local population (40-200 AC). Also the medieval history of inhabitation of the area surrounding the Maasdelta has been investigated in a combined historical-geographical and archaeological way. Thus Rotterdam and Maas-delta surroundings possess soil archives, which cover a period of almost 10.000 years. This archaeological and socio-historical heritage is being threatened by proceeding urbanization and industrialization as well as by landscape operations. The importance of a regional-archaeological approach will only increase.